2017
DOI: 10.1128/jcm.00751-17
|View full text |Cite
|
Sign up to set email alerts
|

Low Cryptococcus Antigen Titers as Determined by Lateral Flow Assay Should Be Interpreted Cautiously in Patients without Prior Diagnosis of Cryptococcal Infection

Abstract: Detection of Cryptococcus antigen (CrAg) is invaluable for establishing cryptococcal disease. Multiple different methods for CrAg detection are available, including a lateral flow assay (LFA). Despite excellent performance of the CrAg LFA, we have observed multiple cases of low-titer (Յ1:5) positive CrAg LFA results in patients for whom cryptococcosis was ultimately excluded. To investigate the accuracy of low-titer positive CrAg LFA results, we performed chart reviews for all patients with positive CrAg LFA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 20 publications
1
25
0
1
Order By: Relevance
“…Of note, our study showed that all false-positive cases were found in low serum titer cases, and more than a half (60.0%, 6/10) of them had predisposing conditions. Likewise, in the investigation by Dubbels et al, one or more co-existing predisposing factors were identified in 4 of 11 false-positive individuals with an overall rate of 36.4% (Dubbels et al 2017). However, the role of the immune status in the diagnostic accuracy of the CrAg LFA test remains unknown, though the incidence of false positives was higher in patients with predisposing factors.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Of note, our study showed that all false-positive cases were found in low serum titer cases, and more than a half (60.0%, 6/10) of them had predisposing conditions. Likewise, in the investigation by Dubbels et al, one or more co-existing predisposing factors were identified in 4 of 11 false-positive individuals with an overall rate of 36.4% (Dubbels et al 2017). However, the role of the immune status in the diagnostic accuracy of the CrAg LFA test remains unknown, though the incidence of false positives was higher in patients with predisposing factors.…”
Section: Discussionmentioning
confidence: 93%
“…With predisposing factors 33.3 CrAg titers were also identified in 20.0% (5/25) proven or probable cryptococcosis patients through an investigation at the Mayo Clinic (Dubbels et al 2017), indicating a potentially high incidence of low CrAg titer in HIV-negative patients, in whom the fungal burden may be lower. Early diagnosis, usually confirmed by CrAg titers in serum or CSF, is crucial for reducing the dissemination, disability and mortality of cryptococcosis (Sungkanuparph et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role CrAg screening in cost‐saving and disease prevention in transplant recipients has been postulated but not yet defined. Further study is needed to determine whether there is an association between low‐positive CrAg titers in this setting and the risk of post‐transplant cryptococcosis, as well as the role of prophylactic antifungal therapy.…”
Section: Discussionmentioning
confidence: 99%